Knee Extensor and Flexor Torque Variability During Maximal Strength Testing and Change in Knee Pain and Physical Function at 60-Mo Follow-Up: The Multicenter Osteoarthritis Study (MOST). (February 2021) - Schroeder, Allison; Wang, Na; Felson, David T.; Lewis, Cora E.; Nevitt, Michael C.; Segal, Neil A.
Abstract : Abstract: As the population ages, there is a growing burden owing to musculoskeletal diseases, such as knee osteoarthritis, and subsequent functional decline. In the absence of a cure, there is a need to identify factors amenable to intervention to prevent or slow this process. The Multicenter Osteoarthritis Study cohort was developed for this purpose. In this study, associations between variability in peak knee flexor and extensor torque at baseline and worsening of pain and physical function over the subsequent 60 mos were assessed in a cohort of 2680 participants. The highest quartile of baseline knee flexor torque variability was found to be associated longitudinally with worsening pain (fourth quartile ß estimate, mean ± SE, 0.49 ± 0.19; P = 0.0115; with R 2 = 0.28 and P for trend across quartiles = 0.0370) and physical function scores (fourth quartile ß estimate, mean ± SE, 1.39 ± 0.64; P = 0.0296; with R 2 = 0.25 and P for trend across quartiles = 0.0371), after adjusting for baseline knee osteoarthritis and maximum knee flexor torque. There were no associations between baseline knee extensor torque and worsening pain or physical function by 60 mos. The presence of greater variability in maximum knee flexor strength may identify patients who may benefit from therapies aimed at preventing worsening knee pain and physical function. Abstract : Supplemental digital content is available in the text.